2020
DOI: 10.1177/1367493520949427
|View full text |Cite
|
Sign up to set email alerts
|

The predictors, barriers and facilitators to effective management of acute pain in children by emergency medical services: A systematic mixed studies review

Abstract: We aimed to identify predictors, barriers and facilitators to effective pre-hospital pain management in children. A segregated systematic mixed studies review was performed. We searched from inception to 30-June-2020: MEDLINE, CINAHL Complete, PsycINFO, EMBASE, Web of Science Core Collection and Scopus. Empirical quantitative, qualitative and multi-method studies of children under 18 years, their relatives or emergency medical service staff were eligible. Two authors independently performed screening and selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 45 publications
(107 reference statements)
1
26
0
1
Order By: Relevance
“…Analgesic administration should be encouraged when indicated, even if the onset time is considered slow, as there are potentially psychosocial benefits in addition to the pharmaceutical effects. A recent systematic review also concluded that efforts to facilitate analgesic administration should take priority 44 . Ambulance services should aim to staff all vehicles with at least one paramedic, necessitating long‐term commitment to developing staff.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analgesic administration should be encouraged when indicated, even if the onset time is considered slow, as there are potentially psychosocial benefits in addition to the pharmaceutical effects. A recent systematic review also concluded that efforts to facilitate analgesic administration should take priority 44 . Ambulance services should aim to staff all vehicles with at least one paramedic, necessitating long‐term commitment to developing staff.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review also concluded that efforts to facilitate analgesic administration should take priority. 44 Ambulance services should aim to staff all vehicles with at least one paramedic, necessitating longterm commitment to developing staff. Clinicians should consider any unconscious (implicit) bias they may have by evaluating "gut" reactions to specific groups of patients and what impact this has on patient care.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…Only the interviewer and interviewee were present during the session. An interview schedule was used as a prompt and to collect field notes (see Additional file 1 ); the development of the interview schedule was informed by our previous systematic review [ 12 ] and the first phase of our mixed methods study [ 2 ]. The interview schedule was pilot tested on the first three participants; no substantial changes were required.…”
Section: Methodsmentioning
confidence: 99%
“…A recent systematic mixed studies review identified and synthesised five qualitative studies assessing the barriers and facilitators to pre-hospital pain management in children [ 12 ]. There were no studies that explored the experiences of children whilst only one study explored the experiences of parents during the ambulance encounter [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are barriers significantly limiting the measures used by ETs to reduce pain (lack of skills to obtain venous access, difficult pain assessment in preverbal children and toddlers, low experience of ETs in treating children, medical interventions at night, short transport time to hospital), the barriers should not justify untreated acute pain in children [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%